Determining the capital structure of Shariah-compliance industrial firms in Malaysia / Zahariah Sahudin … [et al.] - Sahudin, Zahariah; Abdullah, Hasni; Pardi, Faridah; Bahrudin, Nur Zahidah; Hassan, Salwana (Faculty of Accountancy, 2019)
This study highlights the sensitivity of capital structure determinants in each sector within the Shariah-compliant Property firms listed in Bursa Malaysia. Although the proportion of debt financing is similar, each sector adopts different financing patterns. The inconclusiveness of findings and inconsistencies of results on capital structure in the previous literature have remained the core debatable issue in the finance world. This study is primarily motivated by the issue of the scrutinised determinants still being inconclusive in the area of capital structure. The study is conducted using the static models namely Pool Ordinary Least Square, Fixed Effect and Random Effect Model. Empirical analysis on the determinants reveals that country specific factor which is GDP and sector specific factor which is industry concentration are also significant in influencing the corporate financing decisions in this country along with firm specific factors such as profitability, tangibility, liquidity and size of the firm. The findings revealed that results are sensitive to models employed in the study. Nevertheless, the applicability of capital structure theories such as the trade-off theory, agency theory and pecking order theory diverge across sectors in Malaysia. The pecking order theory and agency theory are found to be the dominant theories governing the corporate financing decision in the country as well. It indicates strong evidence of hierarchy practiced in firms’ financing decision. The finding on agency theory being dominant justifies the function of short-term debt as a controlling mechanism to mitigate the agency problem arises within firms across sectors.